2009
DOI: 10.1158/1055-9965.epi-08-1102
|View full text |Cite
|
Sign up to set email alerts
|

TP53 R249S Mutations, Exposure to Aflatoxin, and Occurrence of Hepatocellular Carcinoma in a Cohort of Chronic Hepatitis B Virus Carriers from Qidong, China

Abstract: Hepatocellular carcinoma (HCC) has a high mortality in East Asia and Sub-Saharan Africa, two regions where the main etiologic factors are chronic infections with hepatitis B virus and dietary exposure to aflatoxin. A single base substitution at the third nucleotide of codon 249 of TP53 (R249S) is common in HCC in these regions and has been associated with aflatoxin-DNA adducts. To determine whether R249S may be detected in plasma DNA before HCC diagnosis, we conducted a case-control study nested in a cohort of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 18 publications
1
44
0
1
Order By: Relevance
“…HBV and the dietary aflatoxins have been suggested as the most important HCC hazard factors in China (Li et al, 2001), where HBV infection is almost a prerequisite for the onset of HCC in the high-risk regions (Yeh et al, 1989;Shen et al, 1991). Dietary exposure to aflatoxin B1 (AFB1) (Li et al, 2001;Wang et al, 2001;Wang and Liu, 2007) may associate with HCC risk in Chinese cohorts due to enhancement of the mutation frequency of the third nucleotide of codon 249 of TP53 (Deng et al, 1997;Kirk et al, 2000;Szymanska et al, 2009) and oxidative stress (Wu et al, 2008). However, among R e t r a c t e d individuals at very high risk of liver cancer due to infection with HBV and AFB1 exposure, only 20% eventually develop liver cancers.…”
Section: Introductionmentioning
confidence: 99%
“…HBV and the dietary aflatoxins have been suggested as the most important HCC hazard factors in China (Li et al, 2001), where HBV infection is almost a prerequisite for the onset of HCC in the high-risk regions (Yeh et al, 1989;Shen et al, 1991). Dietary exposure to aflatoxin B1 (AFB1) (Li et al, 2001;Wang et al, 2001;Wang and Liu, 2007) may associate with HCC risk in Chinese cohorts due to enhancement of the mutation frequency of the third nucleotide of codon 249 of TP53 (Deng et al, 1997;Kirk et al, 2000;Szymanska et al, 2009) and oxidative stress (Wu et al, 2008). However, among R e t r a c t e d individuals at very high risk of liver cancer due to infection with HBV and AFB1 exposure, only 20% eventually develop liver cancers.…”
Section: Introductionmentioning
confidence: 99%
“…First, the method using RFLP assay might not be sensitive for detecting R249S mutation in some specimens containing trace amounts of the mutant DNA. In this regard, it has been shown that, at high blood levels of R249S mutation, RFLP provides good results in agreement with more sensitive methods such as short oligonucleotide mass analysis (SOMA) (Szymanska et al, 2009). At low levels, however, the signals generated by RFLP are below the detection threshold and might be responsible for the false-negative results.…”
Section: Discussionmentioning
confidence: 87%
“…We integrated the experimental results from cell lines and mice with somatic-mutation spectra from newly sequenced HCCs from Qidong, China, a region of well-studied high aflatoxin exposure (Szymanska et al 2009;Kensler et al 2011). The HCCs from Qidong were also selected for somatic TP53 R249S mutations, which is considered indicative of AFB1 exposure (Hollstein et al 1991;Montesano et al 1997;Sun et al 2011).…”
Section: Mutation Spectra Of Likely Aflatoxin-associated Human Hccsmentioning
confidence: 99%